1994
DOI: 10.1152/ajpcell.1994.266.4.c1013
|View full text |Cite
|
Sign up to set email alerts
|

Luminal perfusion of isolated gastric glands

Abstract: We have extended to rabbit gastric glands the technique for perfusing single isolated renal tubules. We isolated glands by hand dissection and used concentric glass pipettes to hold them and perfuse their lumina. Parietal cells (PCs), which tended to be located toward the gland opening, were identified by their pyramidal shape, large size, and autofluorescence. Chief cells (CCs) were identified by their round shape and smaller size. In some experiments, we perfused the lumen with hydroxypyrenetrisulfonate, a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 19 publications
3
57
0
Order By: Relevance
“…These were the first membranes shown to have negligible gas permeability. We also found that lowering luminal pH to 1 failed to alter pH i (22). We similarly observed null pH i shifts, rather than the expected pH i increase, when perfusing lumens of gastric gland (24) or colonic crypts (25) In fact, it would be interesting to see whether the apical membranes of the medullary thick ascending limb, like those of the gastric gland, indeed are impermeable to CO 2 and NH 3 .…”
Section: Membranes With Negligible Gas Permeabilitysupporting
confidence: 54%
“…These were the first membranes shown to have negligible gas permeability. We also found that lowering luminal pH to 1 failed to alter pH i (22). We similarly observed null pH i shifts, rather than the expected pH i increase, when perfusing lumens of gastric gland (24) or colonic crypts (25) In fact, it would be interesting to see whether the apical membranes of the medullary thick ascending limb, like those of the gastric gland, indeed are impermeable to CO 2 and NH 3 .…”
Section: Membranes With Negligible Gas Permeabilitysupporting
confidence: 54%
“…The tissues were then transferred to the stage of a dissecting microscope. Individual glands were isolated using a hand dissection technique as described previously (11). After isolation, the glands were allowed to adhere to coverslips precoated with Cell-Tak (Collaborative Research, Bedford, MA) and transferred to a thermostatically controlled chamber maintained at 37°C on either a laser confocal microscope or on a video imaging system for the duration of the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…Following laparotomy a total gastrectomy was performed, and the stomach was immediately rinsed with ice-cold HEPES-buffered Ringer solution (125 mM NaCl, 5 mM KCl, 1 mM CaCl 2 , 1.2 mM MgCl 2 , 32.2 mM HEPES, and 5 mM glucose, pH 7.4) ( Table 1) to eliminate any residual food matter, and kept in HEPES solution on ice until use. 0.5-cm square sections were cut from the corpus and transferred to the stage of a dissecting microscope where individual gastric glands were hand-dissected using a previously described technique (66). After isolation, the glands were transferred to coverslips precoated with adhesive Cell-Tak (BD Cell-Tak Cell and Tissue Adhesion, BD Biosciences) and mounted in a thermostatically controlled chamber maintained at 37°C on an inverted microscope (Olympus IX50) attached to a digital imaging system (Universal Imaging, Downingtown, PA) for the duration of the experiment.…”
Section: Isolation Of Gastric Glands and Digital Imaging For Ph I -mentioning
confidence: 99%